PENDEKATAN DAKWAH WASATHIYYAH FORUM DAKWAH PERBATASAN (FDP) DALAM PEMBINAAN SAUDARA BARU DI WILAYAH PERBATASAN ACEH - Fakhri, Fakhri; Fairus, Fairus; Zuhdi, Ahmad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Abstract: The coaching of converts to Islam has been an important aspect in the border areas of Aceh Province. This program is conducted considering that the region is prone to silting of faith, drug abuse and negative influence of foreign culture, which could affect the faith and aqidah (creed) of Muslim residing in the border area. This issue becomes the background of this study in an attempt to figure out the approaches of dakwa wasathiyyah (moderate) carried out by the organization of Forum Dakwah Perbatasan (FDP) in implementing its coaching programs for the converts to Islam in the border area. This study employed qualitative approach, in which interview and document analysis were used for collecting the data. The result of this study shows that Forum Dakwah Perbatasan (FDP) has performed the Dakwa fundamentally and consistently within the framework of Islam Wasathiyyah to the Muslim society in the border and remote areas of Aceh. The da’i (callers to Islam) of FDP performed the dakwa in accordance with their vision, that Islamic dakwa should be developed based on the tenets of Islam Wasathiyyah. Among the tenets of Dakwa Wasathiyyah conducted by the FDP are; tawazzun, tawasshut, i’tidal, tasamuh, musawah, syura ishlah, aulawiyah, and tathawwur wa ibtikar. While in implementing those dakwa programs, the FDP performed dakwa by using various approaches as follows: dakwa tauhid, social dakwa, transformative dakwa, and humanist dakwa. This study concluded that the FDP has greatly contributed and assisted in strengthening and coaching the aqidah of the converts to Islam in Aceh.Keywords: Dakwa Wasathiyyah; Forum Dakwah Perbatasan; Converts to Islam.Abstrak: Pembinaan saudara baru menjadi aspek penting di wilayah perbatasan Aceh. Mengingat kawasan tersebut rawan terjadinya pendangkalan akidah, peredaran narkoba dan pengaruh budaya asing yang dapat mempengaruhi keyakinan dan akidah umat Islam di perbatasan. Hal inilah yang menjadi latar belakang penelitian ini dengan tujuan untuk mengkaji tentang gambaran pendekatan dakwah Wasathiyyah yang dilaksanakan oleh Forum Dakwah Perbatasan (FDP) dalam pembinaan berbagai program terhadap saudara baru di perbatasan. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data wawancara dan studi dokumentasi. Hasil penelitian menunjukkan bahwa secara prinsipil dan komitmen Forum Dakwah Perbatasan (FDP) telah melakukan dakwah dalam kerangka Islam Wasathiyyah di kalangan umat Islam di perbatasan dan pedalaman Aceh. Para da'i Forum Dakwah Perbatasan (FDP) menjalankan dakwah sesuai dengan visinya di mana dakwah Islam selayaknya dikembangkan dengan konsep Islam Wasathiyyah.Adapun prinsip -prinsip Dakwah Wasathiyyah yang dilakukan Forum Dakwah Perbatasan (FDP), sebagai berikut: tawazzun, tawasshut, i'tidal, tasamuh, musawah, syura ishlah, aulawiyah, dan tathawwur wa ibtikar. Dalam mengimplementasi program dakwah tersebut, Forum Dakwah Perbatasan (FDP) melakukan dakwah dalam berbagai pendekatan, di antaranya: dakwah tauhid, dakwah sosial, dakwah transformatif dan dakwah humanis. Dari penelitian ini dapat disimpulkan bahwa Forum Dakwah Perbatasan (FDP) telah memberikan kontribusi dan andil besar terhadap penguatan dan pembinaan akidah saudara baru di perbatasan Aceh.Kata Kunci: Dakwah Wasathiyyah; Forum Dakwah Perbatasan; Saudara Baru.